Getting the Most Out of the Evidence for Transfusion Medicine - Stanworth, S; Brunskill, S; Doree, C; Hopewell, S; Arnold, D (John Wiley and Sons, 2013)
Reviews have long been used to provide summary statements of the evidence for clinical practice. Systematic reviews aim to be more explicit and less biased in their approach to reviewing a subject than traditional (narrative) literature reviews. There are a large number of published systematic reviews relevant to the broad theme of transfusion medicine, covering topics ranging from the effective use of blood components and fractionated blood components to alternatives to blood components and methods to minimize the need for blood in a surgical setting and to blood safety. However, there are also topic areas where few published systematic reviews exist, especially donation screening and blood donor selection. In paediatric transfusion practice, there is a paucity of evidence from RCTs or systematic reviews on which to base clinical decisions. This edition first published 2013 © 2001, 2005, 2009, 2013 John Wiley and Sons Ltd.